The Enigmatic Fallopian Tube: A More Common Cause of Catheter Malfunction than Previously Recognized. Issue 4 (July 2016) - Gudsoorkar, Prakash S.; Penner, Todd; Jassal, S. Vanita; Bargman, Joanne M.
Successful performance of peritoneal dialysis (PD) depends on a properly functioning PD catheter. Catheter malfunction remains a significant cause of technique failure, especially early in the course of therapy. Common causes of catheter malfunction include catheter displacement, omental or bowel wrapping, and fibrin clots. Less commonly, various intraperitoneal structures have been reported to lead to obstruction, including appendices epiploicae of sigmoid colon and the fallopian tube. Peritoneal dialysis catheter blockage due to fimbriae of the fallopian tube is being recognized as an important cause of catheter malfunction in females due to the increasing availability of diagnostic laparoscopy. We report 5 episodes of catheter malfunction in 4 patients on PD from a single center as a result of obstruction by the fallopian tube.